2022
DOI: 10.3390/w14152435
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Prospective Areas of Water Resources and Monitoring Land Use/Land Cover Changes in an Arid Region Using Remote Sensing and GIS Techniques

Abstract: Groundwater is a vital water resource for economic, agricultural, and domestic purposes in arid regions. To reduce water scarcity in arid regions, recently, remote sensing and GIS techniques have been successfully applied to predict areas with prospective water resources. Thus, this study attempted to spatially reveal groundwater potential zones (GWPZs) and to conduct change detection on the desert fringes of Wadi Asyuti, a defunct tributary of Egypt’s Nile basin in eastern Sahara. Eleven influential groundwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Among them, the use of machine learning to optimize the waveform of radar signals will further improve the ability of radar detection, classification, identification, localization, and tracking [169]. At present, for the monitoring of small water areas, the "Land Pollution" in the radar waveform is the main source of error, and it has become possible to use machine learning to reduce or even eliminate "Land Pollution" [170]. Research on machine learning and processing methods of satellite altimetry signals.…”
Section: Combining Deep Learning With Multi-source Datamentioning
confidence: 99%
“…Among them, the use of machine learning to optimize the waveform of radar signals will further improve the ability of radar detection, classification, identification, localization, and tracking [169]. At present, for the monitoring of small water areas, the "Land Pollution" in the radar waveform is the main source of error, and it has become possible to use machine learning to reduce or even eliminate "Land Pollution" [170]. Research on machine learning and processing methods of satellite altimetry signals.…”
Section: Combining Deep Learning With Multi-source Datamentioning
confidence: 99%
“…GIS and remote sensing (RS) have the potential to be employed for groundwater investigation, as well as for regional predictions [35,36]. Big geographical data may be aggregated and analyzed to forecast and find new water sources by using GIS-based technology and/or data-driven methodologies [37,38]. Several research projects have demonstrated the practicality of combining GIS and RS to locate possible groundwater resource locations [35,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing and image processing mapping have been widely applied in the environmental sciences since the beginning of their development [11], and they continue to be employed in works on water management and vegetation cover. For example, to reduce water scarcity in arid regions, remote sensing and GIS techniques have been successfully applied to predict areas with potential water resources [12,13]. Combined remote sensing, GIS (Geographic Information System)-based frequency ratios, and evidential belief delineate and quantify prospective groundwater areas in a model.…”
Section: Introductionmentioning
confidence: 99%